Vocabulary Enrichment of Form Six Students: Idiomatic Expressions - Milaševičienė, Lina; Bražienė, Nijolė (Jaunųjų mokslininkų darbai, 2017)
Native language is a communication tool through which a nation reveals its culture and human thinking. Idiomatic expressions, significant part of the Lithuanian language, are important in communication and thinking. There are objective and subjective reasons why nowadays idiomatic expressions are rarely used in everyday speech although it is stated in the basic education curriculum that students must be able to recognize and understand idiomatic expressions, know their figurative meaning and use them. Although sufficient theoretical material and practical tasks are provided in the textbook and workbook of the Lithuanian language for form 5 and form 6, the survey showed that 6 formers had difficulty recognizing idiomatic expressions in a text and understanding them, mixed their general and figurative meaning, guessed figurative meaning, could not remember fixed meaning, tried to remember a situation where it had been heard or used. When asked to produce a coherent text with idiomatic expressions the surveyed often used idiomatic expressions beside the point, rewrote provided idiomatic expressions, tried to remember a situation where it had been used, read or heard, could not replace an emotionally neutral word with an idiomatic expression and produce a creative text.